Effect of investment ease facilitation activities on increasing investors in Serang City - Wiranata, Lingga Adi; Anugraheni, Fitria; wahyudi, Wahyudi (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to determine the increase in investors in Serang City before and after the innovation of Investment Ease Facilitation activities and find out the percentage of comparison from 2021 – 2023 or from before the innovation and after the innovation made by DPMPTSP Serang City. Investment has become a hot topic of conversation in recent years because it will positively impact the regional economy. The Serang City Government continues to strive to create innovations to attract business actors, in this case, MSMEs or investors both from within the country and abroad, to invest so that they can improve the economy of Serang City. We conduct research using qualitative descriptive methods. The data used is secondary data. Data analysis techniques are data reduction, data display, and conclusion. The result of this study is the achievement of an increase in the number of investors in the last three years that exceeded the target of investors after the creation of innovations in Investment Ease Facilitation activities, with the number of investors until December 2023 being 11,430 with the issuance of NIB